Understanding Research Novelty and Research Gaps - Remi Chukwudi Okeke (Social Sciences and Education Research Review)
This paper aims to guide researchers in understanding how to strategically position their work within their academic fields while driving innovative contributions. In academic research, the ability to identify novelty and address research gaps is crucial to advancing knowledge and solving real-world problems. The paper explores the distinction between research novelty and research gaps, and presents strategies for recognizing uncharted areas of study while pioneering innovative contributions. It is intended to guide early-career researchers, other academics and scholars, toward a deeper understanding of how to contribute meaningfully to their fields. By examining examples across various disciplines, the paper highlights practical approaches for developing groundbreaking research that not only fills existing gaps but also drives future inquiry.